Pengaruh Pertumbuhan Ekonomi dan Tingkat Kemiskinan Terhadap Outstanding Zakat di Indonesia - Vivin Wulandari; Deky Anwar; Sari Lestari Zainal Ridho; Chintia Romadayanti (AT-TAWASSUTH: Jurnal Ekonomi Islam, 2025)
This study aims to examine the effect of economic growth and poverty rate on outstanding zakat in Indonesia. The research employs a quantitative descriptive approach using panel data collected from the Central Statistics Agency (BPS) and the National Zakat Agency (BAZNAS) covering the period from 2010 to 2024. The data were analyzed using multiple linear regression with the aid of EViews software. The results reveal that the poverty rate has a negative and significant effect on outstanding zakat in Indonesia, while economic growth shows no significant influence. The coefficient of determination (R²) of 0.4896 indicates that nearly half of the variation in outstanding zakat can be explained by changes in the poverty rate. Simultaneously, the F-test results indicate that the overall model is significant (F-statistic = 12.73; Prob(F) = 0.000154 < 0.05). However, the partial test shows that only the poverty rate variable is statistically significant (p = 0.0001), whereas economic growth is not significant (p = 0.3932). The poverty rate coefficient is negative (-3.09E+11), implying that a decrease in poverty tends to increase outstanding zakat. Meanwhile, economic growth does not exhibit a significant relationship, suggesting that GDP growth does not automatically lead to an increase in zakat disbursement. The negative relationship indicates that as poverty decreases, outstanding zakat rises; conversely, when poverty increases, zakat funds are distributed more quickly to the mustahiq (beneficiaries), resulting in a lower remaining zakat balance. In other words, these findings reflect a responsive and linear zakat distribution mechanism aligned with the socioeconomic conditions of society.